Export Competitiveness of Major Agricultural Products in Pakistan: An Assessment Through Revealed Comparative Advantage Indices - Ahmad, Imran; Saboor, Abdul; Hussain, Safdar; Hassan, Fayyaz ul (iRASD Journal of Economics, 2024)
In today’s era, nations are excelling in trade competitiveness and a paradigm shift has already taken place from the narrative of comparative advantage to competitive advantage. A profitable opportunity is present for the agriculture-driven economy to incorporate product diversification & repositioning of agri. commodities to transform competitiveness into a sustainable positional asset. Pakistan is underperforming as far as its export potential is concerned. This study uses revealed competitive advantage (RCA), relative competitiveness (RC) & relative trade advantage index (RTA) to examine different categories of agri. export from 2001 to 2021, using secondary data from credible trade data sources. Rice, dates, mangoes & citrus have demonstrated strong competitive advantages whereas maize, millet & dairy have disadvantages. The blessed comparative advantage in agricultural products marks the untapped potential of foreign earnings. The realignment of agricultural exports on modern footing is needed for export expansion. The study suggested incorporating modern techniques of harvesting and improved SPS measures to avoid unnecessary post-harvest marketable surplus losses. Value addition, structural changes in crop management and provision of marketing extension services are vital for improving export share, generating business opportunities and reducing trade deficit. The current study concludes that Pakistan, as an agriculturally based economy, has a great potential for higher growth of these products; as a result, Pakistan may be able to generate more foreign exchange from these agricultural products.